DAMPAK MANAJEMEN SUMBER DAYA MANUSIA DAN MOTIVASI TERHADAP KINERJA KARYAWAN MELALUI VARIABEL INTERVENING KOMITMEN ORGANISASI - Bambang Aviantono (Bajang Institute, 2022)
This research study aims to examine the effect of human resource management (HRM) policies and motivation on employee performance with organizational commitment as an intermediate or intervening variable in 5 MSME companies in Mustika Jaya sub-district, Bekasi, West Java. This study includes HR policy factors and motivation as independent variables while employee performance factors as the dependent variable. Furthermore, this study aims to determine the role of